2016
DOI: 10.1007/s00586-016-4562-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporary liver and stomach necrosis after lateral approach for interbody fusion and deformity correction of lumbar spine: report of two cases and review of the literature

Abstract: The spine surgeon should be aware of the possibility of postoperative ischemia of the liver and stomach by occlusion of the celiac artery or its supplying branches. Specifically when a large correction of a kyphotic/kyphoscoliotic spine is planed, the surgeon should be alert for an appearance of a MALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Vasiliadis et al reported two cases that developed acute liver and gastric necrosis due to an occlusion of celiac artery, after a spine deformity correction underwent LLIF [52]. The surgeon should be alert for an appearance of a medial arcuate ligament syndrome (MALS) if a large correction for ADS is planed.…”
Section: Visceral and Vascular Complicationsmentioning
confidence: 99%
“…Vasiliadis et al reported two cases that developed acute liver and gastric necrosis due to an occlusion of celiac artery, after a spine deformity correction underwent LLIF [52]. The surgeon should be alert for an appearance of a medial arcuate ligament syndrome (MALS) if a large correction for ADS is planed.…”
Section: Visceral and Vascular Complicationsmentioning
confidence: 99%
“…Rare complications such as celiac trunk occlusion and bowel perforation may also occur. [46] The location of the iliac wing contributes to the riskiness of this surgery, and precludes exposure of the L5–S1 disc space such that L4–5 surgery may be difficult. Therefore, accurate preoperative patient positioning is important.…”
Section: Introductionmentioning
confidence: 99%
“…In the gastrointestinal field, the chronic compression of the CA by the MAL is known as MAL compression syndrome, but the syndrome is rare 7) . Similar to the mechanism of MAL compression syndrome, excessive kyphosis correction also causes acute compression of the CA, leading to multiple organ failure in ACACS [1][2][3]5,6) . Moreover, because of the preoperative stenosis of the CA, we were concerned that this patient was at considerably more risk of developing ACACS 1,3) .…”
mentioning
confidence: 98%
“…Acute celiac artery compression syndrome (ACACS) after surgery for spinal deformity is a rare but severe complication with potentially fatal consequences [1][2][3][4][5][6] . We report a case in which median arcuate ligament (MAL) resection was performed before spinal surgery for preoperative celiac artery (CA) compression.…”
mentioning
confidence: 99%